1987
DOI: 10.1002/1097-0142(19870815)60:4<883::aid-cncr2820600428>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous urography as a prognostic indicator in vesical carcinoma

Abstract: A retrospective analysis of 1378 cases of urinary bladder tumor, showed that unilateral or bilateral ureteric obstruction seen on an intravenous urogram at presentation, was significantly associated with both decreased overall survival and tumor-free interval. A tumor shadow shown on standard projections did not correlate with survival. At 24 months only 35% of the ureteric obstruction group were tumor-free as compared with 65% of the unobstructed group. Survival at 5 years was 27% in the obstructed ureter gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…This difference may be the result of several factors: the method of patient selection, different definition of ureteral obstruction and higher stage of disease at diagnosis. The incidence of ureteral obstruction among the superficial tumor group 4.1%, corresponds to previously published data [3,8]. Impaired renal function demonstrated in this group, speculatively, can be more than an obvious end result of urine flow disturbance, but one of the immediate modifiers of the prognosis in patients with ureteral Obstruction.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…This difference may be the result of several factors: the method of patient selection, different definition of ureteral obstruction and higher stage of disease at diagnosis. The incidence of ureteral obstruction among the superficial tumor group 4.1%, corresponds to previously published data [3,8]. Impaired renal function demonstrated in this group, speculatively, can be more than an obvious end result of urine flow disturbance, but one of the immediate modifiers of the prognosis in patients with ureteral Obstruction.…”
supporting
confidence: 86%
“…Tumorous ureteral obstruction was defined as radiological evidence of urinary flow disturbance in the form of dilated collecting system, or ureter, or long standing obstruction presented as nonfunctioning kidney unit, which could be explained only in direct connection with the bladder tumor [5,8,10]. Two cases of hydronephrosis due to vesicoureteral reflux and small contracted bladder secondary to previous intravesical bacillus Calmette-GuCrin (BCG) instillations and one case of coexisting primary tumor of the ureter were excluded by those criteria.…”
Section: Methodsmentioning
confidence: 99%
“…This is reflected in the poor prognosis of this selected group, only Remove stent at first Proceed to flexible cystoscopy definitive follow-up treatment 17% remained alive at the time of writing. Other authors have also found that hydronephrosis increased the chance of having metastatic disease, having a poorer differentiation of transitional cell cancer and lower tumour-free interval and survival [2,4,10,[12][13][14]. As the TNM classification of cancer remains the gold standard for determining treatment and advising patients on prognosis, it seems inappropriate that such a strong negative prognostic marker as the presence of hydronephrosis in bladder cancer is not included in this staging classification.…”
Section: Discussionmentioning
confidence: 99%
“…However, it does remain unclear as to how the hydronephrosis is caused. Some authors [5,13] suggest in superficial disease, hydronephrosis results by the involvement of the ureteric orifice by intravesical tumour and that local treatment of the tumour can result in hydronephrosis resolution. Furthermore, in muscle invasive disease, ureteral involvement could be by intramural disease or extravesical compression by direct tumour spread or by enlarged lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the obstruction is often accompanied by more widespread disease. An actuarial survival of only 14% was found in patients with ureteric obstruction in contrast to 47% of patients with normal upper urinary tracts [6], and a significant lower survival was reported if the upper urinary tract was abnormal [1,7].…”
Section: Discussionmentioning
confidence: 99%